(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The rehabilitation of extremely low birth weight (500-999 g) newborns represents one of the pressing challenges in modern neonatology. This study investigates the thymus tissues of stillborn and deceased newborns at 22-24 weeks of gestation using multiplex and confocal morphometric methods based on autopsy samples. Utilizing NanoZoomer scanning and QuPath-ImageJ software, the thickness of the cortex and medulla layers, as well as the volumetric indicators of blood vessels, septa, and Hassall’s corpuscles, were analyzed. Results indicate that as thymus weight decreases, the cortical layer thickness reduces from 46.1 ± 0.2 μm to 20.74 ± 0.9 μm, showing a 55% developmental delay, a 57.4-fold reduction in blood vessel volume, and the predominance of stromal elements. These findings reflect degrees of thymic hypoplasia and aplasia, confirming morphological immaturity of the immune system. This research contributes to a deeper understanding of the factors influencing postnatal adaptation and survival in extremely low birth weight newborns.